Powder-scattering-free glue composition for pyrography and powder-scattering-free pyrography process
By using a tackifying component with a particle size of no more than 10μm that works synergistically with the main adhesive component, a powder-free adhesive composition is used to solve the problems of environmental pollution and inkjet printing stability in heat transfer printing, improve the adhesion and durability of the pattern, and simplify the operation process.
Patent Information
- Application Number
- CN202511092673.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-10-31
AI Technical Summary
Existing heat transfer printing processes suffer from environmental pollution and blurred pattern edges caused by hot melt powder. Water-based adhesives used in inkjet printing can easily penetrate the substrate or clog the printhead, affecting the quality of the finished product.
A powder-free adhesive composition is created by using tackifying components with a particle size of no more than 10 μm in synergy with the main adhesive components. It contains waterborne polyurethane and terpene phenolic resin, combined with zirconium catalyst and humectant, and achieves pattern transfer through inkjet printing.
It improves the adhesion and durability of patterns, simplifies the operation process, reduces environmental pollution, prevents glue from penetrating the substrate, and ensures the stability of inkjet printing and the quality of finished products.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of inks, and in particular to a powder-free heat transfer adhesive composition and a powder-free heat transfer process. Background Technology
[0002] Heat transfer printing is a common process for transferring designs onto the surface of textiles and other substrates, widely used in clothing, bags, and other fields. It typically involves creating a design on a release liner, transferring the design to the fabric surface through heat pressing, and then peeling off the waste film, leaving the design printed onto the garment fabric.
[0003] Current white ink heat transfer printing processes use hot melt powder as a crucial auxiliary material. The process involves first printing the design onto a substrate such as PET heat transfer film, then sprinkling hot melt powder onto the substrate, where it adheres to the printed design. Excess powder is then removed by shaking off excess powder. After high-temperature drying, the hot melt powder and printed design are fused together. Finally, a heat press transfers the design onto fabric or other materials. This process is cumbersome, hot melt powder can cause environmental pollution, and the powder application and shaking processes can easily lead to blurred edges or defects in the design, affecting the quality of the finished product.
[0004] Inkjet printing technology directly prints water-based adhesive onto substrates such as PET heat transfer film, eliminating the need for powder application and thus avoiding the environmental pollution caused by hot melt powder. However, it still has some drawbacks: water-based adhesives need to have low viscosity to be compatible with inkjet printers, but low viscosity may cause the adhesive to penetrate the substrate or dry too slowly. If high-viscosity water-based adhesives are used, filler particles may clog the printhead or cause scale buildup on the printhead. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process, which improves the adhesion and durability of the transferred pattern and prevents the adhesive from penetrating the substrate.
[0006] The first aspect of the present invention provides a powder-free heat transfer adhesive composition comprising the following components: a) a main adhesive component; b) a tackifying component, wherein the tackifying component is a particle with a particle size not greater than 10 μm, and the mass ratio of the tackifying component to the main adhesive component is (0.01-0.5):1.
[0007] The adhesive composition of this application significantly improves the adhesion of the adhesive to the substrate and printing material through the synergistic effect of the main adhesive component and tackifying components with specific particle size and proportions. It effectively prevents adhesive penetration into the substrate, shortens curing time, and enhances the wash resistance and durability of the heat transfer printed product. Compared with traditional powder application processes, it eliminates the need for powder application, simplifies operation, is environmentally friendly, and is suitable for various application methods, including inkjet printing.
[0008] Furthermore, the mass ratio of the tackifying component to the main adhesive component is (0.05-0.25):1. This preferred ratio provides better performance.
[0009] Furthermore, the main adhesive component is waterborne polyurethane. Waterborne polyurethane has good film-forming properties and is environmentally friendly, which helps to improve the overall performance and safety of the finished product.
[0010] Furthermore, the waterborne polyurethane is a compound with CAS number 51852-81-4. Using waterborne polyurethane with CAS number 51852-81-4 can further improve the film-forming uniformity and elasticity of the adhesive composition. The adhesive composition can be dispersed on the inkjet pattern layer, promoting the adhesion of the inkjet pattern layer and enhancing the synergistic effect with the tackifying components, thereby giving the transferred pattern higher wear resistance and durability.
[0011] Furthermore, the tackifying component is a terpene phenolic resin. Using terpene phenolic resin as a tackifying component effectively improves the adhesion of the adhesive to the substrate and the printed material. This type of resin exhibits good adhesion to PET (polyethylene terephthalate) films, interacting with the PET surface (e.g., hydrogen bonding, polar adsorption, chemical bonding) to enhance adsorption force. This effectively shortens the curing time of water-based adhesives, significantly improves their bonding performance, prevents penetration into the substrate, and, through excellent polarity and intermolecular forces on the inkjet pattern layer, forms a stronger interfacial bond with the main adhesive component (especially water-based polyurethane with CAS number 51852-81-4), significantly improving the fastness and washability of the transferred pattern.
[0012] Furthermore, the particle size of the tackifying component is 0.3-1 μm. Controlling the particle size of the tackifying component within the range of 0.3-1 μm balances inkjet printing compatibility and the adhesive's tackifying effect. A suitable particle size range helps prevent printhead clogging, ensures smooth inkjet printing, enhances adhesive dispersion and film uniformity, and improves transfer results.
[0013] Furthermore, the adhesive contains a thickener and / or a viscosity modifier. The thickener further includes at least one of hydroxyethyl cellulose (HEC), sodium carboxymethyl cellulose (CMC), alginate, and a polyurethane thickener (such as BYK-410); the viscosity modifier includes at least one of polyvinyl alcohol, nanocellulose, and microfibrillated cellulose. These components help to accelerate the drying speed of the adhesive, improve production efficiency, and enhance adaptability to inkjet printing or other application methods. Furthermore, the mass ratio of thickener to the main adhesive component is (0.2-0.5):1.
[0014] Furthermore, the inkjet catalyst comprises 0.3-1 wt% zirconium-based catalyst. Further, the zirconium-based catalyst comprises at least one of zirconium acetylacetonate (CAS No.: 17501-44-9) and zirconium isopropoxide (CAS: 14717-56-7). The zirconium-based catalyst can promote the bonding of the main adhesive component and the tackifying component after inkjet printing, ensuring both the low viscosity and flowability requirements of inkjet printing, and enhancing film formation after inkjet printing. It effectively inhibits adhesive penetration into the substrate, improving the adhesion, washability, and dry and wet rub fastness of the pattern.
[0015] Furthermore, it includes humectants and deionized water. Humectants and deionized water can regulate the evaporation rate of the adhesive, preventing it from drying out too quickly during storage and application, thus improving the storage stability and application uniformity of the adhesive.
[0016] Furthermore, the humectant includes high-boiling-point humectants and medium-boiling-point humectants, mixed in a volume ratio of (0.2-1):1. High-boiling-point humectants refer to those with a boiling point above 220°C, while medium-boiling-point humectants refer to those with a boiling point between 150-220°C. This prevents the glue from drying too quickly. Specifically, high-boiling-point and medium-boiling-point humectants can be obtained by mixing water and alcohols, or by using different alcohols. High-boiling-point humectants include at least one of triols, glycerin, ethylene glycol butyl ether, and dipropylene glycol; medium-boiling-point humectants include at least one of ethylene glycol, glycerol, and glycerol, or can be obtained by mixing a high-boiling-point humectant with water, such as a 50% (v / v) aqueous solution of triethanolamine with a boiling point of approximately 160°C.
[0017] A second aspect of the present invention provides a heat transfer printing process that eliminates the need for powder application, comprising the following steps: a) forming a pattern layer on the surface of a peelable release substrate; b) applying the above-described adhesive composition to the pattern layer; c) drying and hot-pressing the substrate with a printing substrate to achieve pattern transfer; d) peeling off the release substrate.
[0018] This process requires no powdering, is simple to operate, environmentally friendly, produces finished products with good adhesion and durability, and has a wide range of applications.
[0019] Furthermore, the application step is inkjet printing, which is performed using an inkjet printer. Inkjet printing helps reduce material waste, improves production efficiency, and adapts to complex and diverse pattern design needs.
[0020] The present invention has the following specific beneficial effects: 1. The tackifying components work synergistically with the main adhesive components to form a bond with the pattern layer on the substrate surface, preventing penetration into the substrate and significantly improving the adhesion of the transferred pattern.
[0021] 2. When the mass ratio of the tackifying component to the main adhesive component is (0.01-0.5):1, the adhesive composition improves the tackifying effect of the adhesive while ensuring inkjet printing adaptability, and enhances the adhesion and durability to the substrate.
[0022] 3. When the particle size of the tackifying component is 0.3-1μm, it can ensure good dispersion of the tackifying component in the adhesive, prevent nozzle clogging, ensure continuous and stable inkjet printing process, effectively improve the uniformity and density of film formation of the adhesive on the substrate and pattern layer surface, make the edges of the transferred pattern clear and the colors full, and the finished product has better water resistance and abrasion resistance.
[0023] 4. Adding 0.3-1 wt% of a zirconium-based catalyst to the adhesive composition can significantly improve the curing efficiency and film-forming properties of the adhesive, and enhance the wash resistance, abrasion resistance, and overall adhesion of the transferred pattern. Zirconium-based catalysts (such as zirconium acetylacetonate and zirconium isopropoxide) can promote the cross-linking reaction between the main adhesive component and the tackifying component after inkjet printing, accelerate the drying and curing speed of the adhesive system, inhibit the penetration of the adhesive into the substrate, and improve transfer efficiency. Detailed Implementation
[0024] To facilitate understanding of this application, a more complete description will be provided below. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0026] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0027] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0028] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows for temperature fluctuations within the precision range controlled by the instrument.
[0029] In some preferred embodiments, the mass ratio of the tackifying component to the main adhesive component is (0.01-0.5):1. Specifically, the mass ratio of the tackifying component to the main adhesive component can be selected from any of the following ratios: 0.01:1, 0.05:1, 0.10:1, 0.25:1, 0.4:1, or 0.5:1.
[0030] In some preferred embodiments, the main adhesive component comprises at least one of waterborne polyurethane resin and waterborne acrylic resin.
[0031] In some preferred embodiments, the main adhesive component comprises an aqueous polyurethane resin, specifically CAS number 51852-81-4.
[0032] In some preferred embodiments, the mass ratio of the tackifying component to the main adhesive component is (0.05-0.25):1. Specifically, the mass ratio can be selected from any of the following values: 0.05:1, 0.10:1, 0.15:1, 0.20:1, or 0.25:1.
[0033] In some preferred embodiments, the tackifying component is a terpene phenolic resin.
[0034] In some preferred embodiments, the particle size of the thickening component is 0.3-1 μm. Specifically, the particle size of the thickening component can be selected from 0.3, 0.4, 0.5, 0.7, 0.9, 0.95, and 1 μm.
[0035] In some preferred embodiments, a thickener and / or viscosity modifier are included. Specifically, the thickener includes at least one of hydroxyethyl cellulose (HEC), sodium carboxymethyl cellulose (CMC), alginate, and polyurethane thickeners (such as BYK-410); the viscosity modifier includes at least one of polyvinyl alcohol, nanocellulose, and microfibrillated cellulose.
[0036] In some preferred embodiments, the catalyst comprises 0.3-1 wt% zirconium-based catalyst. Specifically, the mass fraction of the zirconium-based catalyst may be selected from 0.3, 0.4, 0.5, 0.7, 0.9, 0.95, or 1 wt%. Specifically, the zirconium-based catalyst comprises at least one of zirconium acetylacetonate (CAS No.: 17501-44-9) and zirconium isopropoxide (CAS: 14717-56-7).
[0037] In some preferred embodiments, a humectant and deionized water are included.
[0038] In some preferred embodiments, the humectant comprises a high-boiling-point humectant and a medium-boiling-point humectant, which are mixed in a volume ratio of (0.2-1):1.
[0039] Example 1: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process.
[0040] Heat transfer adhesive composition: The main adhesive component is waterborne polyurethane (15wt%, CAS No. 51852-81-4), the tackifying component is terpene phenolic resin particles (Arakawa 803L, particle size 0.5μm, 3.75wt%), the thickener is hydroxyethyl cellulose (0.5wt%, CAS No. 9004-62-0), the viscosity modifier is microfibrillated cellulose (0.2wt%, diameter 100-1000nm, length 20-100μm, Qihong Technology), 1wt% of a mixture of triethanolamine and ethylene glycol (volume ratio 1:1, boiling point about 220℃) as a humectant, and the remainder is deionized water, with all components totaling 100%.
[0041] Conventional heat transfer colored ink and white ink (all commercially available heat transfer colored ink and white ink from Moku New Materials are arbitrarily selected; the same colored ink or white ink is used in each embodiment and comparative example) are printed on a peelable PET film to form a pattern layer. Then, the above-mentioned adhesive composition is applied to the pattern layer by inkjet printing. After drying, the substrate PET film is hot-pressed onto the printing material such as textile fabric. The hot pressing (130°C, 30 seconds) achieves the transfer of the pattern. After cooling, the PET film is peeled off to obtain a complete transfer pattern.
[0042] Example 2: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process. The difference from Example 1 is that the amount of the tackifying component is adjusted to 0.15wt%.
[0043] Example 3: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process. The difference from Example 1 is that the main adhesive component is replaced with water-based acrylic resin.
[0044] Example 4: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process. The difference from Example 1 is that the thickener is replaced with hydroxypropyl methylcellulose.
[0045] Example 5: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process. The difference from Example 1 is that the adhesive composition also contains 1 wt% of a zirconium-based catalyst, which is zirconium acetylacetonate.
[0046] Example 6: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process. The difference from Example 1 is that the adhesive composition also contains 0.3 wt% of a zirconium-based catalyst, which is zirconium isopropoxide.
[0047] Example 7: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process. The difference from Example 1 is that the particle size of the tackifying component is adjusted to 0.9 μm.
[0048] Example 8: This example provides a powder-free heat transfer adhesive composition and a powder-free heat transfer process. The difference from Example 1 is that the water-based polyurethane is changed to YF9654, which is produced by Shanghai Chaozhan Industrial Co., Ltd.
[0049] Comparative Example 1: This comparative example provides a heat transfer adhesive composition and heat transfer process, which differs from Example 1 in that no tackifying ingredients are added.
[0050] Comparative Example 2: This comparative example provides a heat transfer adhesive composition and heat transfer process, which differs from Example 1 in that the amount of tackifying component is only 0.01 wt%.
[0051] Comparative Example 3: This comparative example provides a heat transfer adhesive composition and heat transfer process, which differs from Example 1 in that the particle size of the tackifying component is adjusted to 20 μm.
[0052] Comparative Example 4: This comparative example provides a heat transfer adhesive composition and heat transfer process, which differs from Example 1 in that no main adhesive component is added.
[0053] The samples prepared in the above examples and comparative examples were subjected to performance tests.
[0054] Viscosity test of adhesive composition: The viscosity of the adhesive composition was measured using a single-cylinder rotational viscometer method, in accordance with the national standard GB / T 2794-2013.
[0055] Dry and wet rubbing fastness: The yellow color patch was tested for dry and wet rubbing fastness according to the relevant requirements of GB / T 3920-2008 "Textiles - Tests for Color Fastness - Color Fastness to Rubbing", and the test results were evaluated according to relevant requirements. The test results were compared with the five levels of staining using gray scales, and the level was judged. The higher the level value, the better the rubbing fastness.
[0056] Water wash fastness test: The yellow color patch printed on woven fabric was tested for water wash fastness according to the relevant requirements of GB / T 5713-2013 "Textiles - Tests for Color Fastness - Water Fastness". The test results were evaluated according to relevant requirements. The evaluation of the test results was based on the color difference between the original sample and the sample after fading, using a gray scale to assess the color change. A higher value indicates better water wash fastness.
[0057] Table 1. Test results of the examples and comparative examples.
[0058]
[0059] As shown in Table 1, the data from the examples are significantly better than those from the comparative examples. This is because the adhesive composition of this application, through the synergistic effect of the main adhesive component and the tackifying components of a specific particle size and proportion, significantly improves the adhesion of the adhesive to the substrate and the printed material, effectively prevents the adhesive from penetrating the substrate, shortens the curing time, and improves the wash resistance and fastness of the heat transfer printed product. Comparative Example 1, lacking tackifying components, suffers from poor adhesion, easy penetration, and has the lowest dry and wet rubbing fastness and staining grade. It can also be seen that adding tackifying components in the examples does not lead to an excessive increase in adhesive viscosity. The proportion of tackifying components in Comparative Example 2 is too low, making it difficult to exert the above-mentioned effects. The tackifying particle size in Comparative Example 3 is too large, leading to increased viscosity, uneven dispersion, easy clogging of the nozzle, and poor adhesion. Comparative Example 4, without the addition of the main adhesive component, makes it difficult for the adhesive to form an effective bonding interface between the pattern layer and the surface of the printed material, resulting in significantly reduced fastness and easy penetration.
[0060] Example 3 used acrylic resin, which had lower viscosity and fastness compared to polyurethane. Example 5 used 1 wt% zirconium-based catalyst, which promoted the bonding of the main adhesive component and the tackifier after spraying. This ensured both the low viscosity and flowability required for inkjet printing and enhanced film formation after spraying, effectively inhibiting adhesive penetration into the substrate and improving the adhesion, washability, and dry and wet rub fastness of the pattern. Example 8 used other grades of polyurethane, which could not synergize with the tackifier, resulting in lower performance compared to Example 1.
[0061] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A powder-free heat transfer adhesive composition, characterized in that, It contains the following ingredients: a) Main adhesive component; b) Tackifying component, wherein the tackifying component is a particle with a particle size of no more than 10 μm, and the mass ratio of the tackifying component to the main adhesive component is (0.01-0.5):
1.
2. The adhesive composition according to claim 1, characterized in that, The main adhesive component is water-based polyurethane.
3. The adhesive composition according to claim 2, characterized in that, The waterborne polyurethane is a compound with CAS number 51852-81-4.
4. The adhesive composition according to claim 1, characterized in that, The thickening component is a terpene phenolic resin.
5. The adhesive composition according to claim 1, characterized in that, The particle size of the thickening component is 0.3-1 μm.
6. The adhesive composition according to claim 1, characterized in that, It contains a thickener and / or a viscosity modifier, wherein the thickener is cellulose-based and the viscosity modifier is microfibrillated cellulose.
7. The adhesive composition according to claim 1, characterized in that, It contains 0.3-1 wt% zirconium-based catalyst.
8. The adhesive composition according to claim 1, characterized in that, It contains moisturizers and deionized water.
9. A powder-free heat transfer printing process, characterized in that, Includes the following steps: a) Forming a patterned layer on the surface of a peelable release substrate; b) Applying the adhesive composition according to any one of claims 1-8 onto the patterned layer; c) Dry the substrate and then heat-press it onto the printing substrate to achieve pattern transfer; d) Peel off the release substrate.
10. The heat transfer printing process according to claim 9, characterized in that, The application step is inkjet printing.